PENGGUNAAN MEDIA MAPS BERBASIS DARING UNTUK MENINGKATKAN KEMAMPUAN SPASIAL SISWA - Dyah Lyesmaya; Suci Amelia Putri; Andi Nurrochmah (PGSD Universitas Muhammadiyah Cirebon, 2020)
This study explains the background that contains the subject of an education and a knowledge of knowledge relating to learning Ips, discussion of the Qur'an related to the science of Ips. The purpose of this study is to describe the results obtained from the use of online-based Maps media with students' spatial ability, while a Mpas media measures consisting of (1) preliminary activities, (2) conveying, (3) presenting, (4) explaining , (5) demonstrating (6) the cover. The research design used in this study was the classroom action research (CAR) method. This research method uses a Classroom Action Research with a cycle model developed by Kemmis and MC Taggart. A study was carried out in 2 cycles which in cycle I and II were carried out online. There are two findings here: (1) theoretical benefits explaining the results of this study can be useful for adding insight and developing material in applying online Maps-based media in social studies learning processes in Spatial abilities, (2) practical benefits, practical benefits here are four parts namely (a) for students, (b) for teachers, (c) for schools, (d) for researchers. Keywords: Media Maps, Spatial Capability